Clinical Outcomes of Distraction Arthroplasty with Arthroscopic Microfracture for Advanced Stage Ankle Osteoarthritis. Issue 4 (16th October 2019) - Ikuta, Yasunari; Nakasa, Tomoyuki; Tsuyuguchi, Yusuke; Ota, Yuki; Kanemitsu, Munekazu; Adachi, Nobuo
Category: Ankle Arthritis, Arthroscopy Introduction/Purpose: Ankle trauma is highly implicated in the etiology of osteoarthritis (OA) of the ankle, and posttraumatic ankle OA is often observed in younger patients. In advanced stages, ankle arthrodesis has been considered as a gold standard treatment, and total ankle arthroplasty is also developed over the past decade for older patients. However, the surgical treatment of severe ankle OA for younger, active patients remains challenging. Ankle distraction arthroplasty is an alternative option for treatment of severe ankle OA in younger patients. The distraction device enables joint distraction with ankle motion that induces cartilage repair of the ankle. This study aimed to clarify the clinical outcome of the ankle distraction arthroplasty with arthroscopic microfracture for ankle OA in younger patients. Methods: This retrospective analysis included 7 ankle OA patients who underwent distraction arthroplasty with arthroscopic microfracture, in 5 men and 2 women, with a mean age of 45.9 years (range, 39-62). Range of motion (ROM) and American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot score were evaluated as the clinical outcomes. The talotibial joint space was identified as anterior, center and posterior segment on lateral view. The width of joint space in each segment was measured on pre- and post-operative weight-bearing radiographs. The distraction device was removed at 3 months after initial surgery, and second look arthroscopy was also performed at the same time. The arthroscopic findings were assessed retrospectively. Results: All 7 patients were followed with a mean follow-up period of 4.2 years. One patient who had the worst preoperative AOFAS score of 19 converted to arthroscopic ankle arthrodesis at 2 years after the initial surgery. The mean total ROM and AOFAS score improved from 29.3 to 37.1 (p = 0.028), from 41.7 to 76.1 (p = 0.018), respectively. Weight-bearing radiographs showed a width of ankle joint space with anterior, center and posterior of 1.9 mm, 1.8 mm, 2.0 mm at preoperative status and 2.9 mm, 2.8 mm, 2.9 mm at final follow-up status. Second look arthroscopy revealed that the fibrous cartilage like tissue covered the cartilage defect area at the talotibial joint in all patients. Conclusion: Our findings suggest that the distraction arthroplasty with arthroscopic microfracture could be a useful option for active patients with advanced stage of ankle OA. Good clinical status and the width of joint space had been preserved for a maximum of seven years. Further follow-up was required to elucidate the long-term clinical results.